Reaktualisasi Pendidikan Aqil Baligh di Sekolah - Wahidah Wahidah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
The article discusses how aqil baligh education in schools can be implanted by teachers so that between baligh and aqil parallels hand in hand, there is no gap between the two. Data collection using review literature methods analyzes various information from various writing sources of both books, modules, journal articles and other research results. To implement aqil baligh education in schools can be done by taking three steps. The first step is to make the educational targets that of designing the proper curriculum in order. Which functions are that it parallels biological maturity, psychological and social maturity as well as financial. Second, implementing a project-based learning process that is, a learning model that develops an understanding of concepts through meaningful problem investigation and can produce a real product or real experience such as an internship. Third, learning by creating learning communities through the learning cooperative learning model. The method of cooperative learning is shown to improve learner learning independence.